Dynamic Phycobilin Pigment Variations in Diazotrophic and Non-diazotrophic Cyanobacteria Batch Cultures Under Different Initial Nitrogen Concentrations - Wang, Jingyu; Wagner, Nicole D.; Fulton, James M.; Scott, J. Thad (Frontiers in Microbiology, 2022)
Increased anthropogenic nutrient loading has led to eutrophication of aquatic ecosystems, which is the major cause of harmful cyanobacteria blooms. Element stoichiometry of cyanobacteria bloom is subject to nutrient availabilities and may significantly contribute to primary production and biogeochemical cycling. Phycobilisome is the antenna of the photosynthetic pigment apparatus in cyanobacteria, which contains phycobilin pigments (PBPs) and linker proteins. This nitrogen (N)-rich protein complex has the potential to support growth as a N-storage site and may play a major role in the variability of cyanobacteria N stoichiometry. However, the regulation of PBPs during bloom formation remains unclear. We investigated the temporal variation of N allocation into PBPs and element stoichiometry for two ubiquitous cyanobacteria species, Microcystis aeruginosa and Dolichospermum flos-aquae, in a batch culture experiment with different initial N availabilities. Our results indicated that the N allocation into PBPs is species-dependent and tightly regulated by the availability of nutrients fueling population expansion. During the batch culture experiment, different nutrient uptake rates led to distinct stoichiometric imbalances of N and phosphorus (P), which substantially altered cyanobacteria C: N and C: P stoichiometry. Microcystis invested cellular N into PBPs and exhibited greater flexibility in C: N and C: P stoichiometry than D. flos-aquae. The dynamics of such N-rich macromolecules may help explain the N stoichiometry variation during a bloom and the interspecific difference between M. aeruginosa and D. flos-aquae. Our study provides a quantitative understanding of the elemental stoichiometry and the regulation of PBPs for non-diazotrophic and diazotrophic cyanobacteria blooms.